Pengaruh Storytelling Branding dan Nostalgia Emotion Terhadap Minat Beli Sirup Marjan Ramadhan - J, Junaidi; Pebrianti, Wenny; Shalahuddin, Ahmad; H, Heriyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the impact of storytelling branding on purchase intention, with nostalgia emotion as a mediating variable, using Marjan Syrups Ramadan advertising campaigns over the past three years as the research object. Marjan Syrup, long known as a brand synonymous with Ramadan traditions in Indonesia, has consistently employed storytelling branding strategies to evoke nostalgia among consumers. This research uses a quantitative survey method involving 200 respondents who have seen Marjans Ramadan advertisements in the past three years. The collected data were analyzed using regression and path analysis techniques to examine the relationships between the independent variable (storytelling branding), the mediating variable (nostalgia emotion), and the dependent variable (purchase intention). The results show that storytelling branding positively influences purchase intention, directly and through mediating nostalgia emotion. These findings highlight the importance of emotional narratives in strengthening consumer engagement and driving purchasing behavior, especially in seasonal marketing campaigns.